Domestic Interest Rate and Capital Inflows Policy in Nigeria - Innocent Chile Nzeh; Uche Collins Nwogwugwu; Maria Chinecherem Uzonwanne; Chika Priscilla Imoagwu; Edwin Udochukwu Nwachukwu (Econometric Research in Finance)
The implementation of sterilization policy has been noted to raise domestic interest rates as it is designed to lower money supply. This occurs due to the inverse relationship between money supply and interest rates, with a rise in interest rates attracting additional inflows into the economy, putting pressure on monetary authorities. The verification of this hypothesis in the Nigerian context formed the motivation for this study. The main purpose of this study is to investigate whether sterilization policy actually raises domestic interest rates in Nigeria. Using a monthly dataset from 2010M1 to 2021M3 and the ARDL estimation technique, total sterilization serves as a proxy for sterilization policy, while the treasury bills rate proxies the domestic interest rate. Findings reveal that sterilization policy has a positive and significant impact on domestic interest rates in both the short-run and long-run. Additionally, money supply negatively affects domestic interest rates in the short-run, while world interest rates have a negative and significant impact on domestic rates in both the short and long runs.